Feeding ecology of Mediterranean common dolphins: The importance of mesopelagic fish in the diet of an endangered subpopulation - Joan Giménez; Ana Marçalo; Manuel García‐Polo; Isabel García‐Barón; Juan José Castillo; Carolina Fernández‐Maldonado; Camilo Saavedra; M. Begoña Santos; Renaud de Stephanis (Marine Mammal Science, 2018)
The Mediterranean subpopulation of common dolphin ( Delphinus delphis ) is classified as endangered by the IUCN . Still, information about their diet in the Mediterranean is scarce. Stomach contents of 37 common dolphins stranded in the Alboran Sea and Strait of Gibraltar were analyzed. A total of 13,634 individual prey of 28 different taxa were identified. For fish, Myctophidae was the most important family as indicated by the highest index of relative importance ( IRI = 8,470), followed by the family Sparidae ( IRI = 609). The most important Myctophidae species was Madeira lantern fish ( Ceratoscopelus maderensis ) and for Sparids, the bogue ( Boops boops ). Cephalopods, instead, were found in low quantities only with 31 prey from the Loliginidae, Ommastrephidae, and Sepiolidae families. Overall, our results indicate that common dolphins are mainly piscivorous (99.77% N , 94.59% O , 99.73% W ), feeding mostly on mesopelagic prey. Although common dolphins inhabit mainly coastal waters in the study area, the narrow continental shelf seems to facilitate the availability of Myctophids and other members of the mesopelagic assemblage to dolphins when the assemblage migrates to the surface at night. Our results represent the first attempt at quantifying the diet of this predator in the Alboran Sea and Strait of Gibraltar.